2011
DOI: 10.1089/met.2010.0117
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome and Its Individual Components: Its Association with Venous Thromboembolism in a Mediterranean Population

Abstract: We conclude that, in subjects with a mean age of 44 years, metabolic syndrome increases VTE risk, although abdominal obesity is the pivotal factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…The inter-observer agreement for the study selection was excellent, with a k of 0.92. After the selection process, eight studies were eligible for this analysis (15,17,18,19,20, 21,22,23), six were case-control studies (15,17,18,21,22,23) and two were prospective cohort studies (19,20). All contacted investigators agreed to provide their full database of the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inter-observer agreement for the study selection was excellent, with a k of 0.92. After the selection process, eight studies were eligible for this analysis (15,17,18,19,20, 21,22,23), six were case-control studies (15,17,18,21,22,23) and two were prospective cohort studies (19,20). All contacted investigators agreed to provide their full database of the study.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of these risk factors results in a significantly increased risk of developing coronary artery disease and ischemic stroke (14). Recent studies suggest that the metabolic syndrome may also be associated with VTE (15-21), but several issues remain unclear. In particular, whether this association is attributable to the metabolic syndrome or to abdominal obesity alone, with no additional contribution by the other components, and whether this association is gender specific remain to be established (19,20).…”
mentioning
confidence: 99%
“…Previous studies have shown that obesity plays a pivotal role in the development of VTE related to MS [18,19]. Steffen et al [20] found MS was associated with incident VTE, but this was attributed to obesity instead of the other MS components.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Moreover, the incidence of venous thromboembolism correlates with epicardial fat thickness 7 and abdominal obesity. 8 Additional important risk factors for venous thromboembolism in obese patients include inflammation, decreased fibrinolysis, increased thrombin generation, and platelet hyperactivity. 9 Interventions such as diet, exercise, and gastric bypass surgery not only result in weight loss and reduced visceral adipose tissue mass, but also improve insulin sensitivity, delay the onset of T2D, and prevent cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%